2020
DOI: 10.21203/rs.2.17433/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative Efficacy of Neuraxial and General anesthesia for hip fracture surgery: A meta-analysis of randomized clinical trials

Abstract: Abstract Background: The choice of anesthesia technique remains debatable in patients undergoing surgical repair of hip fracture. This meta-analysis was performed to compare the effect of neuraxial (epidural/spinal) versus general anesthesia on perioperative outcomes in patients undergoing hip fracture surgery.Methods: Medline, Cochrane Library, Science-Direct, and EMBASE databases were searched to identify eligible studies … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
4
1
Order By: Relevance
“…There is varied and conflicting evidence in the literature regarding the effect of regional anesthesia on mortality in this population. Several meta-analyses published since 2015 have reported no significant differences in 30-day mortality between patients who receive regional or GA [10,13,14] . The current review did not find a significant difference in 30-day mortality but did identify a reduced risk of in-hospital mortality for those receiving regional anesthesia.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…There is varied and conflicting evidence in the literature regarding the effect of regional anesthesia on mortality in this population. Several meta-analyses published since 2015 have reported no significant differences in 30-day mortality between patients who receive regional or GA [10,13,14] . The current review did not find a significant difference in 30-day mortality but did identify a reduced risk of in-hospital mortality for those receiving regional anesthesia.…”
Section: Discussioncontrasting
confidence: 52%
“…There is varied and conflicting evidence in the literature regarding the effect of regional anesthesia on mortality in this population. Several meta-analyses published since 2015 have reported no significant differences in 30-day mortality between patients who receive regional or GA. [10,13,14] The current review did not find a significant difference in 30-day mortality but did identify a reduced risk of in-hospital mortality for those receiving regional anesthesia. Of note, 2 recent meta-analyses by Chen et al [51] and Van Waesberghe et al [9] reported nearly identical outcomes following hip fracture surgery; they found no differences in 30-day mortality between groups, but reported a decrease of in-hospital mortality when neuraxial anesthesia was used instead of GA. [9,51] Mean length of hospital stay for those undergoing this type of procedure is estimated to be 6.2 days.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Questions could arise if this difference in the percentage of patients operated on with spinal anaesthesia could be of influence on the end result. However, until now the literature is not unambiguous about the advantages and disadvantages of spinal and general anaesthesia in hip fracture patients (46).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with some studies (19,42), this reduction was not found in the present study. Other studies showed a reduction of complication rates after the introduction of geriatric co-management, although the percentages and kinds of complications differ per study (43)(44)(45)(46). Also here, a selection or information bias can be created by more thorough examinations by geriatricians compared to surgeons and more detailed patient files.…”
Section: Effect Of the Care Pathway On Complicationsmentioning
confidence: 90%